2017
DOI: 10.1016/j.mcat.2016.12.010
|View full text |Cite
|
Sign up to set email alerts
|

A fluorescence active catalyst support comprising carbon quantum dots and magnesium oxide doping for stabilization of palladium nanoparticles: Application as a recoverable catalyst for Suzuki reaction in water

Abstract: Novel magnesium oxide-carbon quantum dots have been synthesized and used for the formation and stabilization of palladium nanoparticles. This highly water dispersible material, Pd@MgO-CQD, has been used as an active catalyst for Suzuki coupling of aryl bromides at room temperature and aryl chlorides at 80 °C in water. Using fluorescence emission of the material, a new protocol for determine of Pd loading and leaching in catalyst preparation and recycling process was developed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
17
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 48 publications
(19 citation statements)
references
References 42 publications
2
17
0
Order By: Relevance
“…Furthermore, materials MWCNT‐imi‐Pd 3 and CNH‐imi‐Pd 5 were subjected to XPS analysis (Figure ) to estimate the degree of reduction of palladium after the treatment with NaBH 4 . The results, summarized in Table , showed how the degree of reduction was quite similar for both materials, with the content of Pd(0) being equal to 61% and 63% for MWCNT‐imi‐Pd 3 and CNH‐imi‐Pd 5 , respectively . Moreover, it is worth noting that although the palladium loading of material 3 is slightly higher than that of 5 (7.6 vs. 7.1 wt%), the Pd/C atomic ratio determined by XPS is the same, revealing a higher surface exposure of Pd NPs in the latter hybrid (Table ).…”
Section: Resultsmentioning
confidence: 82%
“…Furthermore, materials MWCNT‐imi‐Pd 3 and CNH‐imi‐Pd 5 were subjected to XPS analysis (Figure ) to estimate the degree of reduction of palladium after the treatment with NaBH 4 . The results, summarized in Table , showed how the degree of reduction was quite similar for both materials, with the content of Pd(0) being equal to 61% and 63% for MWCNT‐imi‐Pd 3 and CNH‐imi‐Pd 5 , respectively . Moreover, it is worth noting that although the palladium loading of material 3 is slightly higher than that of 5 (7.6 vs. 7.1 wt%), the Pd/C atomic ratio determined by XPS is the same, revealing a higher surface exposure of Pd NPs in the latter hybrid (Table ).…”
Section: Resultsmentioning
confidence: 82%
“…In order to confirm the addition of creatine, XPS spectrum of a region of N 1s was studied, and results showed an intense peak at 400 eV related to the nitrogen of creatine (Figure a) . The XPS spectrum in the Pd 3d region showed the presence of two intense doublets at 335.6 and 340.9 eV related to Pd(0) and peaks at 337.7 and 342 eV related to Pd(II) corresponding to Pd 3d 5/2 and Pd 3d 3/2 , respectively (Figure b) …”
Section: Resultsmentioning
confidence: 99%
“…reported a zwitterionic precursor for in situ generated Pd‐nanoparticles and catalysis therein at 80 °C with six recycle runs. Fluorescence active supports (MgO‐doped carbon quantum dots) were used to stabilize and visualize (easily map) the distributed Pd‐nanoparticle as reusable catalysts in water as reported by Najera et al . In most of these cases it was observed that the performance of the formed catalysts (turnover frequencies, TOFs) were typically low to moderate.…”
Section: Figurementioning
confidence: 99%